ANT-MAN. SEASON ONE - DeFalco, Tom; Domingues, Horacio (New York : Marvel Enterprises, 2012)
"A husband to a murdered wife. A son to a disapproving father. A scientist disgraced and undercut by his rivals. Before he began his life of super heroics as the original Avenger called Ant-Man, Hank Pym was a man lost in other indentities. Now, legendary writer Tom DeFalco (Amazing Spider-Man) and acclaimed artist Horacia Domingues (Fantastic Four: True Story) bring you the untold story of how the man the Marvel Universe has known as Ant-Man, Giant-Man, Goliath and Yellowjacket grew from a tortured lost soul into one of Earth's Mightiest Heroes."--Provided by publisher.
Keywords: Ant-Man (Fictitious character) -- Comic books, strips, etc; Superheroes -- Comic books, strips, etc; Superheroes; Comic books, strips, etc; Graphic novels